2014
DOI: 10.1002/oby.20686
|View full text |Cite
|
Sign up to set email alerts
|

A text messaging‐assisted randomized lifestyle weight loss clinical trial among overweight adults in Beijing

Abstract: Objective The impact of a text messaging‐assisted lifestyle weight loss intervention on weight change among overweight adults in Beijing was examined. Methods It was a 6‐month randomized two arm clinical trial. The control group received a brief advice session after randomization. The intervention group received three group sessions, five coaching calls, and a daily text message prompting participants to follow predetermined lifestyle goals. Results A total of 123 participants were randomized. At 6 months, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(96 citation statements)
references
References 16 publications
2
94
0
Order By: Relevance
“…In addition to chronic disease management, text message support has been used in the public health arena for smoking cessation programs (17), sex education, STD/HIV prevention (18), and adherence to sunscreen usage (19). Success with regard to weight loss has been shown in a domestic pilot study as well as in several studies in other countries (12,14,(19)(20)(21)(22)(23)(24)(25)(26). A recent study showed efficacy of text messaging in cardiac risk factor reduction in participants with cardiovascular disease (27).…”
Section: Discussionmentioning
confidence: 94%
“…In addition to chronic disease management, text message support has been used in the public health arena for smoking cessation programs (17), sex education, STD/HIV prevention (18), and adherence to sunscreen usage (19). Success with regard to weight loss has been shown in a domestic pilot study as well as in several studies in other countries (12,14,(19)(20)(21)(22)(23)(24)(25)(26). A recent study showed efficacy of text messaging in cardiac risk factor reduction in participants with cardiovascular disease (27).…”
Section: Discussionmentioning
confidence: 94%
“…Four studies were excluded because the control group received an intervention with technology aspect (Carter, Burley, Nykjaer, & Cade, 2013;Laing et al, 2014;Shaw et al, 2013;Steinberg, Levine, Askew, Foley, & Bennett, 2013). Twenty-seven trials met inclusion criteria (Agras, Taylor, Feldman, Losch, & Burnett, 1990;Allen, Stephens, Dennison Himmelfarb, Stewart, & Hauck, 2013;Appel et al, 2011;Blomfield et al, 2014;Burke et al, 2012;Cadmus-Bertram et al, 2013;Chambliss et al, 2011;Collins et al, 2012;Donaldson, Fallows, & Morris, 2014;Goulis et al, 2004;Harvey-Berino et al, 2010;Haugen, Tran, Wyatt, Barry, & Hill, 2007;Herring, Cruice, Bennett, Davey, & Foster, 2014;Hutchesson et al, 2014;Jeffery et al, 2003;Johnston, Massey, & DeVaneaux, 2012;Lin et al, 2014;Luley, Blaik, Reschke, Klose, & Westphal, 2011;Mehring et al, 2013;Morgan, Lubans, Collins, Warren, & Callister, 2011;Napolitano, Hayes, Bennett, Ives, & Foster, 2013;Norman, Kolodziejczyk, Adams, Patrick, & Marshall, 2013;Sherwood et al, 2006;Sherwood, Jeffery, Welsh, Vanwormer, & Hotop, 2010;Shuger et al, 2011;Svetkey et al, 2008;Tanaka, Adachi, Adachi, & Sato, 2010) and were included in this review. The total study selection process is shown in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…Most studies were conducted in the United States of America (N ¼ 18) (Agras et al, 1990;Allen et al, 2013;Appel et al, 2011;Burke et al, 2012;Cadmus-Bertram et al, 2013;Chambliss et al, 2011;Goulis et al, 2004;Harvey-Berino et al, 2010;Haugen et al, 2007;Herring Jeffery et al, 2003;Johnston et al, 2012;Napolitano et al, 2013;Norman et al, 2013;Sherwood et al, 2006Sherwood et al, , 2010Shuger et al, 2011;Svetkey et al, 2008). Four studies were conducted in Australia (Blomfield et al, 2014;Collins et al, 2012;Hutchesson et al, 2014;Morgan et al, 2011), one study in China (Lin et al, 2014), one study in Japan (Tanaka et al, 2010), one study in the United Kingdom (Donaldson et al, 2014) and two studies in Germany (Luley et al, 2011;Mehring et al, 2013). The study populations consisted of overweight or obese adults.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adherence to text messaging represents a predictor for weight loss; in other words, if participants respond to text prompts, they tend to lose more weight than others [34]. Social media are a useful device for connecting people taking part in treatments.…”
Section: Self-monitoring and New Technologiesmentioning
confidence: 99%